Summary of the main remote sensing techniques used in volcanoes for monitoring gas emissions on surface - Rodríguez, Lizzette A. (2015)
Volcano monitoring seeks to better understand volcanic systems, in order to be able to predict their activity.  The monitoring techniques include seismic, deformation, gas, hydrologic, and visual monitoring, among others. Gas monitoring is important, among other reasons, because it provides information about the dynamics and evolution of magmatic and hydrothermal systems. Measurements can be conducted directly or by remote sensing methods (ground-based or satellite-based). Here we focus on the main ground-based remote sensing methods, which are currently used at volcanoes. These include the correlation spectrometer (COSPEC), the DOAS, the ultraviolet camera, and the Fourier Transform Infrared spectrometer (FTIR). Each technique has its advantages and disadvantages, and to understand them, we describe here the general aspects of each one, including methods to conduct the measurements, the sources of error, and some examples of case studies.